2023
DOI: 10.1002/alz.13444
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the emergence of amyloid and tau burden in Down syndrome

Matthew D. Zammit,
Tobey J. Betthauser,
Andrew K. McVea
et al.

Abstract: INTRODUCTIONAlmost all individuals with Down syndrome (DS) will develop neuropathological features of Alzheimer's disease (AD). Understanding AD biomarker trajectories is necessary for DS‐specific clinical interventions and interpretation of drug‐related changes in the disease trajectory.METHODSA total of 177 adults with DS from the Alzheimer's Biomarker Consortium‐Down Syndrome (ABC‐DS) underwent positron emission tomography (PET) and MR imaging. Amyloid‐beta (Aβ) trajectories were modeled to provide individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 75 publications
1
4
0
Order By: Relevance
“…Amyloid deposition increased in the parenchyma (amyloid PET) and in the vasculature (microbleeds) at ages 35 and 36 years, respectively. Increased tau deposition in early Braak regions was also observed at 35 years, which is consistent with previous studies showing tau deposition in adults with Down syndrome who were amyloid-negative but accumulating amyloid over time 35 , suggesting that the emergence of amyloid and tau pathology are tightly linked together in time 36 , 37 . Tau deposition in middle and late Braak regions were later at 39 and 37 years, respectively.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Amyloid deposition increased in the parenchyma (amyloid PET) and in the vasculature (microbleeds) at ages 35 and 36 years, respectively. Increased tau deposition in early Braak regions was also observed at 35 years, which is consistent with previous studies showing tau deposition in adults with Down syndrome who were amyloid-negative but accumulating amyloid over time 35 , suggesting that the emergence of amyloid and tau pathology are tightly linked together in time 36 , 37 . Tau deposition in middle and late Braak regions were later at 39 and 37 years, respectively.…”
Section: Discussionsupporting
confidence: 91%
“…To investigate this somewhat unexpected finding, we ran a sensitivity analysis excluding one individual with a very low late Braak SUVR (< 0.5) at an older age, which may have biased the age trajectory after the inflection point lower and pushed the inflection point earlier; however, the estimated age inflection point in late Braak regions was very similar (37.5 [29.1, 45.9]). Longitudinal within-subject data in adults with Down syndrome demonstrated that middle Braak regions accumulate tau prior to late Braak regions according to the amyloid cascade 36 White matter hyperintensities emerged at 35 years old across the brain. The temporal ordering observed is consistent with previous work in late onset AD that demonstrated that greater WMH are associated with tau burden in middle and late Braak regions, but not early Braak regions 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the first clinical trial (NCT05462106) testing an Aβ vaccine in DS participants is underway [64], and there may be future trials testing Aβ immunotherapies already showing promising results in sporadic AD subjects. However, compared to sporadic AD, the formation of tau tangles is much more rapid following the deposition of Aβ plaques in DS [65,66], and thus effective therapeutics targeting pathological tau in DS will be required due to the condensed trajectory of AD pathogenesis. Given the intracellular localization of tau NFTs, immunotherapy approaches are unlikely to succeed, thus emphasizing the need to develop small molecule therapeutics.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the first clinical trial (NCT05462106) testing an Aβ vaccine in participants with DS is underway [ 67 ], and there may be future trials testing Aβ immunotherapies that are already showing promising results in individuals with sAD. However, the formation of tau tangles after the deposition of Aβ plaques is much more rapid in DS than in sAD [ 68 , 69 ]; thus, effective therapeutics targeting pathological tau in DS will be required due to the condensed trajectory of AD pathogenesis. Given the intracellular localization of tau NFTs, immunotherapy approaches are unlikely to succeed, emphasizing the need to develop small-molecule therapeutics.…”
Section: Discussionmentioning
confidence: 99%